دراسة أنماط أضداد النوى لدى المرضى إيجابيّ أضداد النوى في قسم الأمراض الباطنة في مشفى تشرين الجامعي - حسن, عبد الرزاق (Latakia University Journal -Medical Sciences Series, 2018)
The antinuclear antibody (ANA) test is the most commonly used test to screen for autoimmune diseases. However، only limited numbers of studies have addressed the relationship between the patterns of ANA antibodies and the final diagnosis of patients positive for ANA. We aimed to clarify the relationship between the types of ANA antibodies، and the final diagnosis. Patients who visited Internal department at Tishreen University Hospital during the period from January 2017 to December 2017 and were positive for ANA test were enrolled. ANA titers and the final diagnoses were recorded and analyzed. A total of 100 patients were included in this study. We found a relationship between the ANA pattern and the final diagnosis، and this may be of high value in evaluating patients with positive ANA in our everyday clinical practice. يعتبر اختبار أضداد النوى اختبار المسح الأكثر شيوعاً للأمراض المناعية الذاتية وبكل الأحوال فأن عدد محدود من الدراسات درس العلاقة ما بين أنماط أضداد النوى والتشخيص النهائي في المرضى إيجابيّ أضداد النوى. هدفنا من هذه الدراسة إيضاح العلاقة ما بين أنماط أضداد النوى والتشخيص النهائي. تم دراسة المرضى إيجابيّ أضداد النوى المراجعين لمشفى تشرين الجامعي في الفترة الممتدة من كانون الثاني 2017 حتى كانون الأول 2017. تمت تسجيل وتحليل نمط أضداد النوى والتشخيص النهائي حيث شملت هذه الدراسة 100 مريض. وجدنا أن هناك علاقة ما بين نمط أضداد النوى والتشخيص النهائي وهذا قد يكون له أهمية كبيرة في تقييم المرضى إيجابيّ أضداد النوى في الممارسة السريرية اليومية.